PENGARUH KESADARAN KESELAMATAN TERHADAP KINERJA KESELAMATAN KONSTRUKSI - Thanu Harry Khatulistiwa; Rossy Armyn Machfudiyanto (Construction and Material Journal, 2026)
The construction industry in Indonesia faces significant risk challenges related to the high number of work accidents. Despite the implementation of the Construction Safety Management System (SMKK) as regulated by the Minister of Public Works and Housing Regulation No. 10/202, the trend of workplace accidents continues to increase significantly every year. This shows a significant gap between regulations and implementation in the field due to a lack of attention to individual factors, especially workers’ safety awareness, as low safety awareness among construction workers significantly contributes to workplace accidents. This study aims to identify safety awareness indicators, analyze their influence on safety performance, and formulate strategies to enhance safety awareness levels among construction workers. In this research, safety awareness is structured into four main variables: safety climate, safety culture, safety knowledge, and safety behavior. Safety performance is measured using leading and lagging indicators. The study employs a quantitative approach by distributing questionnaires to experts and workers engaged in building construction projects. The results of the analysis demonstrate that most of the proposed indicators effectively form safety awareness and influence safety performance, consisting of 4 variables and 28 indicators. These findings are expected to serve as a guideline for construction project management in achieving more optimal safety performance in the future.